THE ACCESSIBILITY ANALYSIS OF COVID-19 REFERRAL HOSPITALS TO THE LOCATION OF FUNDAMENTAL STUDENT - Bella Theo Tomi Pamungkas; Arfita Rahmawati (Universitas Sebelas Maret (UNS), 2021)
The Covid-19 pandemic that occurred in all parts of the world has had an impact on the various sectors. Not only in the economic sector but also in the educational sector. Until Month June Year 2020, the Indonesian government had carried out a new-normal policy. The purpose of the study was to analyze the affordability of the Covid-19 referral hospital to the position of students during the new-normal era. The affordability could be observed by the distance traveled by students to the nearest Covid-19 referral hospital. This study used the OD matrix layer from ArcMap 10.3. The sample used in this study was 87 students with 11 Covid-19 referral hospitals in East Nusa Tenggara Province. Based on the research results in the form of maps produced, showed that from 87 students observed, only 59 or 67.82% could reach the Covid-19 referral hospitals. Meanwhile, the other 28 students or 32.18% couldn’t be reached by the hospitals. The amount of students observed, located less than 15 km from the Covid-19 referral hospitals were 35 or 40.22% from the total of 87 students. The hospital which students refer to based on their location was the WZ. Yohanes hospital.